7th European Conference on Speech Communication and Technology (Eurospeech 2001) 2001
DOI: 10.21437/eurospeech.2001-586
|View full text |Cite
|
Sign up to set email alerts
|

From here to utility - melding phonetic insight with speech technology

Abstract: An historic tension exists between science and technology with respect to spoken language. Over the coming decades this tension is likely to dissolve into a collaborative relationship melding linguistic knowledge with machine-learning and statistical methods as a means of developing mature science and technology pertaining to human-machine communication. In the process many mysteries surrounding the form and substance of spoken language are likely to be solved through the concerted efforts of scientists and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Providing a structure for accomplishing specific research goals is exceedingly important, but the means by which the objectives are fulfilled are often best left to the imagination and creative devices of individual scientists (cf. [3] and [4]). In today's speech-technology environment such "structured freedom" is rare indeed, thus reducing the probability of truly innovative research coming to the fore(front).…”
Section: Beyond Freedom and Disciplinementioning
confidence: 99%
“…Providing a structure for accomplishing specific research goals is exceedingly important, but the means by which the objectives are fulfilled are often best left to the imagination and creative devices of individual scientists (cf. [3] and [4]). In today's speech-technology environment such "structured freedom" is rare indeed, thus reducing the probability of truly innovative research coming to the fore(front).…”
Section: Beyond Freedom and Disciplinementioning
confidence: 99%
“…In particular, it is shown that accent affects the onset, nucleus and coda elements of the syllable differentially. Such information could be of utility in modeling pronunciation variation for automatic speech recognition [5] [6] and text-to-speech applications.…”
Section: Introductionmentioning
confidence: 99%